Fiscal Rules, Public Investment, and Growth - Servén, Luis (World Bank, Washington, DC, 2012)
Solvency is an intertemporal concept, relating to the present value of revenues and expenditures, and encompassing both assets and liabilities. But the standard practice among policy makers, financial market participants and international financial institutions is to assess the strength of the fiscal accounts solely on the basis of the cash deficit. Short-term cash flows matter, but a preponderant focus on them can encourage governments to invest too little, especially during episodes of fiscal tightening. This has potentially adverse consequences for growth and, paradoxically, even for fiscal solvency itself. The paper offers an overview of the links between fiscal targets, public investment, and public sector solvency. After reviewing the international experience with public investment under fiscal adjustment, the paper lays out an analytical framework to illustrate the consequences of using the public deficit as a guide to solvency. The paper then discusses some alternatives to conventional cash deficit rules and their implications for investment and fiscal solvency.